2017
DOI: 10.1155/2017/7097580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cobalt Chloride, a Hypoxia-Mimetic Agent, on Autophagy and Atrophy in Skeletal C2C12 Myotubes

Abstract: Background Hypoxia-induced autophagy and muscle wasting occur in several environmental and pathological conditions. However, the molecular mechanisms underlying the effects of the hypoxia-mimetic agent CoCl2 on autophagy and muscle atrophy are still unclear. Methods C2C12 myotubes were exposed to increasing concentrations of CoCl2 for 24 hours. Quantitative RT-PCR, Western blotting, and transmission electron microscopy were performed to confirm autophagy occurs. Autophagy proteins were measured to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 28 publications
5
44
0
Order By: Relevance
“…and LC3II/I ratio rose, while the p62 level declined) [39,40]. Moreover, the levels of LC3 and Beclin1 in C2C12 myotubes are enhanced by exposure to the hypoxic modulator CoCl2 and inhibitors of autophagy promote the expression of myogenin and formation of myotubes [41]. Furthermore, similar to our observations, another investigation found that 8 weeks of resistance ladder training under normoxia reduces the LC3II/LC3I ratio and elevates the level of p62 [42].…”
Section: Resistance Training Alleviates Hypoxia-induced Muscle Atrophsupporting
confidence: 86%
“…and LC3II/I ratio rose, while the p62 level declined) [39,40]. Moreover, the levels of LC3 and Beclin1 in C2C12 myotubes are enhanced by exposure to the hypoxic modulator CoCl2 and inhibitors of autophagy promote the expression of myogenin and formation of myotubes [41]. Furthermore, similar to our observations, another investigation found that 8 weeks of resistance ladder training under normoxia reduces the LC3II/LC3I ratio and elevates the level of p62 [42].…”
Section: Resistance Training Alleviates Hypoxia-induced Muscle Atrophsupporting
confidence: 86%
“…SCSP-505) in 5% CO 2 at 37°C. The markers of C2C12 differentiation model were myogenin and myosin heavy chain [46,47], and the differentiation model was also established in the early work of our laboratory [23,48,49].…”
Section: Cell Culture and Establishment Of The C2c12 Differentiation mentioning
confidence: 99%
“…It has been also demonstrated that Co-induced hypoxic signaling resulted in autophagy and atrophy in C2C12-derived mouse myotubes via the HIF-1α/BNIP3/beclin-1 and AMPK/ mTOR signaling pathways (Chen et al, 2017).…”
Section: Mechanisms Of Physiological Functionmentioning
confidence: 98%